High Temperature Oxidation Behavior of Conventional and Nb-Modified MAR-M246 Ni-Based Superalloy - Alkmin, L. B.; Chaia, N.; Utada, S.; Cormier, J.; Baldan, R. [UNESP]; Coelho, G.; Nunes, C. A. (Springer Nature, 2021)
The present investigations focused on the thermal oxidation of two variants of MAR-M246 alloy having the same contents of Ta and Nb in at. pct, considering the effects of total replacement of Ta by Nb. The alloys were produced by investment casting using high purity elements in induction furnace under vacuum atmosphere. The alloys were oxidized pseudo-isothermally at 800 °C, 900 °C and 1000 °C up to 1000 hours under lab air. Protective oxidation products growing on the surface of the oxidized samples were mainly Al2O3, Cr2O3. Other less protective oxide such as spinels (NiCr2O4 and CoCr2O4) and TiO2 were also detected as oxidation products. The conventional alloy exhibited slight internal oxidation at 800 °C and an enhanced resistance at 900 °C and 1000 °C. The Nb-modified alloy presented an exacerbated internal oxidation and nitridation at 900 °C and 1000 °C and an enhanced resistance at 800 °C. At 1000 °C, Nb-modified alloy was particularly affected by excessive spalling as the main damage mechanisms. From a kinetic point of view, both alloys exhibit the same behavior at 800 °C and 900 °C, with kp values typical of alumina forming alloys (2 × 10−14 to 3.6 × 10−13 g2 cm−4 s−1). However, Ta modified alloys exhibited superior oxidation resistance at 1000 °C when compared to the Nb modified alloy due to better adherence of the protective oxide scale.